IDENTIFICATION OF BUILDING DENSITY USING UAV MAPPING METHOD IN CENTRAL KALIMANTAN REGIONAL SETTLEMENT INFRASTRUCTURE - Pongdatu, Dennis Euro; Ghozy Salahudin, Kholiq; Mokhamad Nur, Cahyadi; Dwi Anggoro, Primasetya (Journal of Marine-Earth Science and Technology, 2022)
The increased population density in urban areas has caused buildings density that need to be identified to find out the development and growth of an area that requires clear planning. This research is using aerial mapping method to produce orthophoto area of Garuda - Tingang street. The on-screen digitation was carried out based on the aerial photo data result to determine the number of buildings and the total area of the building. Then, the classification of land cover vegetation and built up land were carried out. From the data processing, 1641 buildings were found on Garuda – Tingang street. The total area of the building is 35,478 hectares. Based on the Decree of the Minister of Public Works No.378/KPTS/1987, Appendix No.22 has a low building density level. The results of the classification state that the vegetation class has a total percentage of 42,969% and the built-up land class has the percentage of 57.031%.